Molliberus albae gen. et sp. nov., the oldest Laurasian soldier beetle (Coleoptera: Cantharidae) from the Lower Cretaceous Spanish amber. (November 2018) - Peris, David; Fanti, Fabrizio
Abstract: A new soldier beetle (Coleoptera: Cantharidae), Molliberus albae gen. et sp. nov., is described and illustrated from the El Soplao Lower Cretaceous (lower Albian) amber deposit in northern Spain. This is the first fossil species in the family to be described from the Spanish amber and the oldest representative in Europe. The new species shows affinities with the Late Cretaceous (early Cenomanian) species from Myanmar, and the fossil is compared with the other Cretaceous fossil species. The elongate prognathous head is a diagnostic character of Molliberus albae gen. et sp. nov., from which it may be inferred that this species fed on pollen or nectar. Highlights: A new soldier beetle is described from the El Soplao Cretaceous amber (Spain). Molliberus albae is the oldest representative of Cantharidae in Europe. The elongate prognathous head in this specimen is a diagnostic character. Molliberus albae fed on pollen or nectar.